Mangrove dynamics evaluation at Matang Mangrove Forest Reserved by multi-temporal satellite imageries / Nurul Asyikin Ibharim, Muhammad Akmal Roslani and Muzzneena Ahmad Mustapha - Ibharim, Nurul Asyikin; Roslani, Muhammad Akmal; Ahmad Mustapha, Muzzneena (UiTM Press, 2024)
Mangrove ecosystems support a wide range of terrestrial and marine organisms by offering sustenance, reproductive habitats, and nurturing environments. The Matang Mangrove Forest Reserve (MMFR), spanning over 40,000 ha, poses challenges in effectively managing and evaluating the entire area. Hence, remote sensing techniques are employed to effectively monitor and map the temporal fluctuations of land use and land cover occurring within mangrove forest areas. In this study, dynamics over nine (9) years (2011 to 2020) of the mangrove ecosystem were evaluated using RapidEye 2011 and Landsat 8 (OLI) 2020 satellite imageries. Change detection was implemented using pixel-by-pixel modelling analysis. The present study revealed the conversion of mangrove area to waterbody at 4625.1 ha (16.7%), dryland forest at 1886.1 ha (6.8%), and oil palm plantations at 186.9 ha (0.7%). The area conversion was attributed to erosion, logging operations, the establishment of aquaculture facilities, and agricultural practices. Hence, the acquisition of data pertaining to the present condition of mangrove forest species, as well as the temporal fluctuations in the study area, holds significant importance for all stakeholders involved in the preservation of this ecosystem.